2016
DOI: 10.1002/2016gl068009
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of submesoscale flows in the ocean surface boundary layer

Abstract: A signature of submesoscale flows in the upper ocean is skewness in the distribution of relative vorticity. Expected to result for high Rossby number flows, such skewness has implications for mixing, dissipation, and stratification within the upper ocean. An array of moorings deployed in the Northeast Atlantic for 1 year as part of the experiment of the Ocean Surface Mixing, Ocean Submesoscale Interaction Study (OSMOSIS) reveals that relative vorticity is positively skewed during winter even though the scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
127
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 122 publications
(151 citation statements)
references
References 41 publications
15
127
1
Order By: Relevance
“…The prevalence of these motions in more quiescent regions of the ocean remains unresolved. The results presented in this study provide direct observational evidence, complimentary to Buckingham et al (2016), that submesoscale motions are active throughout the ocean, at least during certain times of the year.…”
Section: Introductionsupporting
confidence: 73%
See 3 more Smart Citations
“…The prevalence of these motions in more quiescent regions of the ocean remains unresolved. The results presented in this study provide direct observational evidence, complimentary to Buckingham et al (2016), that submesoscale motions are active throughout the ocean, at least during certain times of the year.…”
Section: Introductionsupporting
confidence: 73%
“…This approximation is justified because the horizontal length scale resolved by the glider is on the order of 4 km, and recent analyses of high-resolution numerical models (Brannigan et al 2015) show that the flow is in geostrophic balance down to scales of 5 km. Furthermore, Buckingham et al (2016) show from the mooring data that the Rossby number associated with these scales, calculated from the inner moorings, has values jRoj , 0.5. The application of these approximations allows q bc to be written in a more compact form:…”
Section: B Potential Vorticity Calculationmentioning
confidence: 94%
See 2 more Smart Citations
“…Both of these mechanisms could explain the results of Capet et al [12] and Klein et al [3] who demonstrated in numerical simulations of the California Current system and a baroclinically-unstable zonal flow respectively, that submesoscale processes favor the generation of cyclonic vortices with Ro larger than one. These results also hold in observations for open ocean regimes in which the fluid motion does not feel any additional constraints due to changes in the water column depth [37]. Here we explore the robustness of these asymmetries in topographically-controlled flows.…”
Section: Introductionsupporting
confidence: 71%